China in the twenty-first century : politics, economy, and society (United Nations University Press, 1997)
China has experienced tremendous change during the era of the People's Republic, particularly during the past 15 years, a period in which it has begun a shift from a centrally planned economy to a market-oriented system. This book, based on an international symposium held at Aoyama Gakuin University, Tokyo, attempts to form a picture of the landscape of China in the twenty-first century.
Keywords: ASEAN.; China -- Economic conditions -- 1976-2000.; China -- Politics and government -- 1976-; Economic forecasting -- China -- Congresses.; China -- Economic conditions -- 1976-2000 -- Congresses.; China -- Social conditions -- 1976-2000 -- Congresses.; Prévision économique -- Chine -- Congrès.; Chine -- Conditions économiques -- 1976-2000 -- Congrès.; Chine -- Politique et gouvernement -- 1976- -- Congrès.; Chine -- Conditions sociales -- 1976-2000 -- Congrès.; Chine -- Conditions économiques -- 1976-2000.; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Comparative.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; Social conditions; Economic forecasting; Economic history; Politics and government; China; Wirtschaft; Gesellschaft; Politik; Economische groei.; Economische situatie.; Sociaal-economische ontwikkeling.; Prévision économique -- Chine.; Prévision sociale -- Chine.; Chine -- Politique et gouvernement -- 1976- ...; Chine -- Conditions sociales -- 1976-2000.; ECONOMIC DEVELOPMENT.; ECONOMIC REFORM.; INDUSTRIAL REDEPLOYMENT.; AUTOMOBILE INDUSTRY.; STOCK COMPANIES.; SOCIAL DEVELOPMENT.; CHINA.; NEW INTERNATIONAL ECONOMIC ORDER.; DEMOCRACY.; Since 1976; Congress; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings.; Actes de congrès.